CircACTG1 Promotes Hepatocellular Carcinoma Progression by Regulating miR-940/RIF1 Axis and Activating AKT/mTOR Pathway. (19th June 2022) - Wu, Chunchen; Tian, She; Guo, Yuting; Yu, Chao; Lei, Linhan; Zheng, Dijie; Xie, Huahua; Zheng, Jian; Sun, Chengyi
Abstract : Background . Hepatocellular carcinoma (HCC) is recognized as the fourth in incidence and the third in mortality worldwide. The onset of HCC is insidious and often asymptomatic at the early stage. HCC is more prone to metastasis, recurrence, and drug resistance than other solid tumors owing to its feature of high heterogeneity. Therefore, what particularly important is to search for effective molecular markers in the occurrence and progression of HCC. Aim . To probe into the therapeutic potential of circACTG1 (hsa_circ_0046144) in HCC cell migration and invasion, providing a new insight and molecular target to diagnose and cure HCC patients. Methods . The circACTG1 expression in collected HCC cells was determined by quantitative polymerase chain reaction (qPCR). Assessment for circACTG1 diagnosing capability was analyzed by receiver operating characteristic (ROC) curves. Transwell assay, wound healing assay, and cell counting kit-8 assay were used for monitoring the effect of circACTG1 in HCC cell invasion, migration, and proliferation, respectively; qPCR, luciferase reporter assay, databases, and Western blot analysis were used for identifying the modulation mechanisms among circACTG1, miRNA-940, and RIF1. What is more, our study verified AKT-mTOR signaling after miR-940 mimic treatment or circACTG1 knockdown. Results . circACTG1 was overexpressed in HCC cells and tissues. Knockdown of circACTG1 restrained 97H and Huh7 cell migration and invasion. Significantly, circACTG1 was discovered to serve as a miR-940 sponge. miR-940 activation rebated the circACTG1 level, and conversely, miR-940 inhibition boosted the circACTG1 level. However, this effect or relationship was not seen after circACTG1 mutation. Furtherly, miR-940-downregulated expression was also found in HCC patients, and importantly, miR-940 inhibition reversed circACTG1 expression in 97H cells with circACTG1 knockdown. Moreover, the expression of RIF1 was significantly reduced after inhibiting circACTG1 or overexpressing miR-940 but rescued when both circACTG1 and miR-940 were inhibited. Finally, circACTG1 and miR-940 played significant roles of regulating AKT-mTOR signaling. Conclusion . circACTG1 expression remarkably ascended in HCC, which is of certain diagnostic value. Moreover, circACTG1 potentially regulates HCC cell proliferation, invasion, and migration via miR-940/RIF1/AKT/mTOR pathway.